Facilitating children's learning in the EYFS - Langston, Ann (Maidenhead, Berkshire, England Open University Press, 2013)
This book will address a range of issues pertinent and prominent in the revised EYFS including brain development; school readiness; engaging parents; and the rationale behind the new prime and specific areas of learning.
Half title; Title; Copyright; Praise for this book; Contents; Figures; Tables; Introduction; 1 The revised EYFS: A principled framework?; 2 School readiness; 3 The significance of child development in the revised EYFS; 4 Engaging parents in children's learning; 5 A pedagogy of care and education; 6 Teaching and learning in the Prime Areas: Birth to three; 7 Teaching and learning in the Prime Areas: From three to five; 8 Literacy; 9 Mathematics; 10 Understanding the world; 11 Expressive arts and design; 12 Teaching beyond the EYFS: A curriculum for the twenty-first century?; References; Index.
Keywords: Early childhood teachers -- Great Britain; Early childhood education